2019
DOI: 10.11591/ijeecs.v14.i1.pp96-100
|View full text |Cite
|
Sign up to set email alerts
|

Normal and abnormal red blood cell recognition using image processing

Abstract: <p>In medical field, the recognition of red blood cells (RBC) are used as an indicator to detect the type of diseases such as anaemia, malaria and leukaemia etc. The problems using manual detection of normal and abnormal RBCs under the microscope is tend to give inaccurate result and errors. This paper proposed a method to recognize the normal and abnormal shaped RBCs image by using Form Factor as feature descriptor. Detecting normal cells of RBCs indicate a healthy patient and abnormal cells indicate pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…This architecture achieved an average accuracy of 93%. In Aliyu et al (2019) , normal and abnormal RBCs were identified by leveraging Form Factor, Perimeter, and area features, achieving an accuracy of 94%. However, the method was ineffective when dealing with noisy images.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This architecture achieved an average accuracy of 93%. In Aliyu et al (2019) , normal and abnormal RBCs were identified by leveraging Form Factor, Perimeter, and area features, achieving an accuracy of 94%. However, the method was ineffective when dealing with noisy images.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Likewise, through images, you can also detect diseases such as anemia. A method was proposed to recognize images of normal and abnormally shaped red blood cells using the shape factor, perimeter, and area as feature descriptors [9]. Also, the design of a finger probe for non-invasive diagnosis of anemia in children, had a satisfactory result, for which several tests were performed, in which the detection of anemia depended basically on blood cells [10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, to automatically classify the types of abnormal RBCs, information on various features of RBCs quantified through mathematical formulas, support vector machine (SVM), and decision tree (DT) classifier models is utilized (Gulati et al, 2013). In previous studies related to the foregoing the amount of computation increases, and the classification time is relatively long because the RBCs are categorized through formula calculation (Aliyu et al, 2019; Divina et al, 2020; Gulati et al, 2013).…”
Section: Introductionmentioning
confidence: 99%